O estudo em grupos para a 2ª fase da OBMEP 2013 e resoluções de questões em vídeo - Dias, Edgar Heliodoro Vendramelli (Universidade Federal de São Carlos, 2014)
This dissertation presents the study done on Municipal School Professor Valdomiro Casagrande, town of Dois Córregos SP about the Brazilian Mathematical Olympiad of Public Schools (OBMEP 2013), working with study groups who sought a better preparation of students for the proof of the second phase in 2013. The dissertation was developed using Didactic Engineering, passing through the steps of previous analyses, a priori concepts, application of experience and a posteriori analyses. This work presents the results obtained with these study groups, awards won by students in 2013 and also the results obtained in the motivational issue much required for mathematic education. Still on the work, are made critical analysis of issues of proof of OBMEP 2010, OBMEP 2011, OBMEP 2012 and OBMEP 2013 (first and second phases), with students and teachers feedback about the content addressed in evidence and with the mathematical theory that each one presented. The work presents the making of an educational DVD, non-profit, with resolutions of issues of OBMEP 2013 (second phase) elaborated by the participating students of the second phase and by the school Mediator, DVD which will be exposed in the Blog of the school and Will serve as material for dissemination of OBMEP 2014 at school and in the municipality.
Keywords: Matemática - estudo e ensino; OBMEP; Grupos de estudos; DVD educativo; OBMEP; Mathematic; Study group; Educational DVD; CIENCIAS EXATAS E DA TERRA::MATEMATICA